Chemical Composition and Amylose Content in Local Rice Variety from Phatthalung Rice Research Center - ชีพประสพ, เชาวนีพร; สาเหล็ม, หาสันต์; อโนมุณี, ฤทัยทิพ (Progress in Applied Science and Technology, 2017)
In this study the chemical composition and amylose content of 22 local rice varieties from the Phatthalung Rice Research Center were determined. The results reviewed that the average contents of moisture, ash, lipid, protein and carbohydrate were 2.47%, 1.41%, 1.76%, 7.56% and 76.81%, respectively. In addition, the average of vitamin B1 content was 0.55 mg/100 g. All 22 local rice varieties were classified into four groups based on amylose content: waxy group (0-9%: Khaoneawdamhmo, Khaoneawlangpingdang, Khaoneawlanta and Khaoneawdamchomipi), low amylose (10-19%: Khaobauhom), intermediate amylose (20-25%: Khaochojangvad, Khaopakow, Khaocholamud, Khaohmoarun and Khaofai) and high amylose (>25%: Khaonanghom, Khaoyathri, Khaoneawlungpung, Khaohomjan, Khaonang, Khaochojampa, Khaojetae, Khaohom, Khaomalidang, Khaotangwai, Khaohakya and Khaosrirak). These results are basic information supporting for cultivation, preservation and product processing of local rice in the future.